Vertical Transmission of Wolbachia Is Associated With Host Vitellogenin in Laodelphax striatellus - Guo, Yan; Hoffmann, Ary A.; Xu, Xiao-Qin; Mo, Pei-Wen; Huang, Hai-Jian; Gong, Jun-Tao; Ju, Jia-Fei; Hong, Xiao-Yue (Frontiers in Microbiology, 2018)
Wolbachia in host germ lines are essential for their vertical transmission to the next generation. It is unclear how the regulation of host oocyte development influences Wolbachia location and the mechanistic basis of transmission. Here, we investigated whether vitellogenin influences Wolbachia transmission in Laodelphax striatellus. Wolbachia increased in density and spread from the anterior tropharium to developing oocytes as ovaries developed. Microscopic observations indicated that Wolbachia invaded ovarioles from the tropharium of its anterior side rather than the pedicel side. Wolbachia utilized the host Vg transovarial transportation system to enter the ovaries and were transmitted from the tropharium into the developing oocytes through nutritive cords. These observations were supported by knocking down the Vg transcript, in which low Wolbachia titers were detected in ovaries and fewer Wolbachia were transmitted into oocytes. Our findings establish a link between the Vg-related mode of transovarial transmission and efficient maternal transmission of Wolbachia.